Right heart failure considerations in pediatric ventricular assist devices. (5th March 2021) - Law, Sabrina P.; Morales, David L. S.; Si, Ming‐Sing; Friedland‐Little, Joshua M.; Joong, Anna; Bearl, David W.; Bansal, Neha; Sutcliffe, David L.; Philip, Joseph; Mehegan, Mary; Simpson, Kathleen E.; Conway, Jennifer; et al.
Abstract: Right heart failure (RHF) is a vexing problem in children after left ventricular assist device (LVAD) implantation that can negatively impact transplant candidacy and survival. Anticipation, prevention, early identification and appropriate medical and device management of RHF are important to successful LVAD outcomes. However, there is limited pediatric evidence to guide practice. This pediatric‐focused review summarizes the relevant literature and describes the harmonized approach to RHF from the Advanced Cardiac Therapies Improving Outcomes Network (ACTION). This review seeks to improve RHF outcomes through the sharing of best practices and experience across the pediatric VAD community.